2008
DOI: 10.1002/jclp.20486
|View full text |Cite
|
Sign up to set email alerts
|

Predicting individual differences in autonomy‐connectedness: the role of body awareness, alexithymia, and assertiveness

Abstract: Autonomy-connectedness is the capacity for being on one's own as well as for satisfactorily engaging in interpersonal relationships. Associations have been shown between autonomy-connectedness components (self-awareness, sensitivity to others, and the capacity for managing new situations) and various indices of psychopathology. Both in a theoretical sense as well as for enhancing treatment and prevention, it is relevant to identify which factors most powerfully predict individual differences in autonomy-connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 51 publications
0
33
0
2
Order By: Relevance
“…The previous vignette reveals an example of a child who appears to have difficulties effectively communicating his feelings regarding his parents' divorce and other troubling events in his life. Jaime may be experiencing a condition called alexithymia, a term first coined by Sifneos (1973) to describe a person's inability to recognize and express feelings (Bekker, Croon, van Balkom, & Vermee, 2008). Research has linked alexithymia to posttraumatic stress disorder (PTSD), depression, panic disorders, and eating disorders (Vanheule, 2008).…”
mentioning
confidence: 99%
“…The previous vignette reveals an example of a child who appears to have difficulties effectively communicating his feelings regarding his parents' divorce and other troubling events in his life. Jaime may be experiencing a condition called alexithymia, a term first coined by Sifneos (1973) to describe a person's inability to recognize and express feelings (Bekker, Croon, van Balkom, & Vermee, 2008). Research has linked alexithymia to posttraumatic stress disorder (PTSD), depression, panic disorders, and eating disorders (Vanheule, 2008).…”
mentioning
confidence: 99%
“…This is in line with our results highlighting the relation between the Anxious attachment style and a higher level of emotional awareness. Moreover, anxiously attached individuals are particularly sensitive to others and there is evidence to suggest that the more sensitive one is to others, the more one is aroused by emotion-inducing events (Bekker, Croon, van Balkom, & Vermee, 2008). Furthermore, research focusing on empathy (the ability to identify and express one’s own emotions and those of others is regarded as a component of empathy) has similarly demonstrated that anxious people experience a higher level of emotional empathy than secure or dismissing individuals (Sonnby-Borgstrom & Jonsson, 2004; Trusty & Ng, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although a clear definition is rarely provided [1], [2], body awareness involves an attentional focus on and awareness of internal body sensations. The term has traditionally been used in studies of anxiety and panic disorders to describe a cognitive attitude characterized by an exaggerated patient focus on physical symptoms, magnification (“somatosensory amplification”), rumination, and beliefs of catastrophic out-comes [3].…”
Section: Introductionmentioning
confidence: 99%